The killing tide [large type] - Pettrey, Dani (Pettrey, Dani. Coastal guardians, 2019)
A Coast Guard officer is found dead, another goes missing, and special agent Finn Walker faces his most dangerous assignment yet. Investigative reporter Harper Grace is determined to discover if the Coast Guard is stonewalling the truth. Can they ignore the sparks between them and track down this elusive killer?